REDUCING THE CLOCKWISE-ALGORITHM TO k LENGTH CLASSES - Marco Ripà (Diponegoro University, 2021)
In the present paper, we consider an optimization problem related to the extension in k-dimensions of the well known 3x3 points problem by Sam Loyd. In particular, thanks to a variation of the so called “clockwise-algorithm”, we show how it is possible to visit all the 3^k points of the k-dimensional grid given by the Cartesian product of (0, 1, 2) using covering trails formed by h(k)=(3^k-1)/2 links who belong to k (Euclidean) length classes. We can do this under the additional constraint of allowing only turning points which belong to the set B(k):=(0, 3) x (0, 3) x ... x (0, 3).